Architectural Morphology and potential use of renewable energy at urban and building scale - Ajmat, Raul Fernando (2017)
The environmental impact generated by the residential sector on energy consumption is estimated at approximately 40%. Architecture and urban planning practice is on the front line directly applying best-case evidence-based solutions to make the most of conserving and generating energy. The excessive and inevitable growth of cities derived in both high and low rise building in most of urban central areas to accomplish social and regular housing demands. Simultaneously, a sustained development of clean energy production technologies and computer simulation allows for an increasingly more precise/accurate prediction of the potential that the architectural morphology possesses on the production of clean energies. High rise buildings bring together: possibilities of high density housing, daylighting access limitations in low floor apartments and issues related with the exploitation of solar irradiation for renewable energy purposes. Today?s powerful building simulation tools can be leveraged for energy modeling during early design phases and even to shape the morphology of tomorrow?s cities. For further reductions in building energy consumption, energy simulations done during conceptual design have potential to impact long term energy use both in architecture and urban planning. This paper reviews early conceptual designs of buildings and their interaction with the immediate built environment looking at the consequences in terms of daylight availability and the potential of irradiation use for clean energy generation.